2019
DOI: 10.1007/s10029-019-01924-w
|View full text |Cite
|
Sign up to set email alerts
|

Two-year patient-related outcome measures (PROM) of primary ventral and incisional hernia repair using a novel three-dimensional composite polyester monofilament mesh: the SymCHro registry study

Abstract: Purpose This study examined patient-related outcome measures (PROMs) after repair of ventral primary or incisional hernias using Symbotex™ composite mesh (SCM), a novel three-dimensional collagen-coated monofilament polyester textile. Methods Pre-operative, peri-operative, and post-operative data were obtained from the French “Club Hernie” registry with 12- and 24-month follow-up. Results One-hundred consecutive patients (mean age 62.0 ± 13.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…In conclusion, the 12-month results of this prospective multi-center study reveal good clinical results and patient outcomes obtained with OviTex 1S Permanent RTM, comparable to and in some cases better than those reported for other mesh materials. Specifically, the recurrence rate appears to be in line or lower than reported in studies with similar populations in the literature [30][31][32][33]. In our experience, the addition of the polymer to the biologic mesh does not appear to increase the risk of mesh infection.…”
Section: Discussionsupporting
confidence: 80%
“…In conclusion, the 12-month results of this prospective multi-center study reveal good clinical results and patient outcomes obtained with OviTex 1S Permanent RTM, comparable to and in some cases better than those reported for other mesh materials. Specifically, the recurrence rate appears to be in line or lower than reported in studies with similar populations in the literature [30][31][32][33]. In our experience, the addition of the polymer to the biologic mesh does not appear to increase the risk of mesh infection.…”
Section: Discussionsupporting
confidence: 80%
“…LVHR required average time of 40 minutes and hospital stay of 2 days which is comparable to Gillion et al who had average time of 43.4 minutes and 2.5day hospital stay. 8 Despite 2 surgeries our patients had only mild pain by 7th post-operative day Lipere et al also reported significant pain reduction by 8th postoperative day. 9 We had mild seroma formation in 50 % cases which resolved with compression dressing only.…”
Section: Discussionmentioning
confidence: 47%
“…Elective hernia surgery shows to have a low rate of mortality being reported by many studies. [13,14] Comorbidity, type of surgery (elective or emergency), clinical type of hernia (simple or complicated), and outcome of surgery in the elderly subjects show a strong association among them. Early elective surgery is recommended in elderly patients to avoid morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Complications at some stage because of reluctance for operation and it has been pointed out in many studies that the mortality and morbidity increase many folds if such hernias are operated in an emergency in elderly patients. [13][14][15][16][17] Comorbidities with the presence of…”
mentioning
confidence: 99%